Competency of Science Vocational Teachers in the Industrial Revolution 4.0 Era - Arif Jatmiko; Gunadi Gunadi (Postgraduate, University of Mataram, 2023)
Vocational education is used to prepare students to be ready to work both in their own environment or in the community, so the main mission of educators and policy makers is to form a strong foundation for students in the learning process, mastery and application of academic skills and the application of concepts that needed. The purpose of this study is vocational teacher competence in the era of industrial revolution 4.0 in SMKN 1 Sei Menggaris and vocational teacher competency in Indonesia today, especially in SMKN 1 Sei Menggaris. The method used in descriptive qualitative research, with data analysis techniques is the Interactive Model Analysis. The results of the research obtained are first: Competencies needed by Science vocational teachers in the current industrial revolution era 4.0 are global language mastery, teamwork, having competencies in accordance with DUDI, mastery of technology with familiarize themselves with ICTs using ICT, mastering teacher competencies, can teach effectively, have competencies in management and class organization, organize learning both theory and practice, and integrate theory with practice. Both vocational teacher competencies have been well implemented at Wonosari Vocational High School 2.